2022
DOI: 10.1108/jcefts-09-2021-0057
|View full text |Cite
|
Sign up to set email alerts
|

Corporate board gender, institutional strength and energy disclosure in Nigeria

Abstract: Purpose The study aims to evaluate the impact of corporate board gender on the energy disclosure with moderating effect of institutional strength (global competitiveness index) by the listed firms in Nigeria. Design/methodology/approach The study uses a sample of 49 non-financial firms listed on the floor of the Nigerian stock exchange commission for the period of five years (2016–2020). The study uses content analysis techniques to obtain data on environmental disclosure through the use of Global Reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…According to Wang et al [90], female directors in Chinese companies promote environmental innovation by incorporating stakeholder-oriented values and beliefs into decision making. Several scholars have backed up these claims, including Radu et al [91], who claim that within the Canadian context, women directors on boards tend to express concerns about social and environmental issues; Jibril et al [92] discussed how energy disclosure and board gender diversity significantly correlated in the Nigerian context. Wang, Yekini, Babajide and Kessy [87] contest that, within the UK context, board gender diversity is significantly and favorably connected with CSR disclosure, while Park et al [93] believe that the feasibility of voluntary carbon emissions disclosure in Korea is increased by gender diversity.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…According to Wang et al [90], female directors in Chinese companies promote environmental innovation by incorporating stakeholder-oriented values and beliefs into decision making. Several scholars have backed up these claims, including Radu et al [91], who claim that within the Canadian context, women directors on boards tend to express concerns about social and environmental issues; Jibril et al [92] discussed how energy disclosure and board gender diversity significantly correlated in the Nigerian context. Wang, Yekini, Babajide and Kessy [87] contest that, within the UK context, board gender diversity is significantly and favorably connected with CSR disclosure, while Park et al [93] believe that the feasibility of voluntary carbon emissions disclosure in Korea is increased by gender diversity.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Among the reasons behind this pressure is the uncertainty that organizations face, so managers give in to this pressure to minimize search and experimentation costs and avoid risks in the adoption of strategies and innovations (Lui et al , 2021; Samad et al , 2021; Teo et al , 2003). This pressure relies on imitating the relevant behaviours of other organizations to stabilize the structure the same and maintain their competitive advantages (DiMaggio and Powell, 1983; Jibril et al , 2022), especially those that represent a high level of success (Liu et al , 2010; Lui et al , 2021).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…However, recent studies established positive and significant associations between energy disclosure and attainment of SDG 7 (Buniamin, 2021; Bergamo, 2022; Jibril et al , 2022a; Wang et al , 2022). The findings of these studies revealed that energy disclosure led to use a firm’s energy efficiently which is essential for the firm to select renewable energy sources for combating present and future climate change and for mitigating overall negative environmental effects in society by achieving SDGs (Setyowati, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%